Empowering human resources and its impact on enhancing business outcomes: "An analytical study of the opinions of a sample of the employees of the Department of Unified National Card Affairs in the holy Karbala" - Hamoudi Al Attar, Fouad; Mitham Abd Al- Ali, Sief (Iraqi Journal for Administrative Sciences, 2024)
The research aims to identify the empowerment of human resources in the Department of Unified National Card Affairs in the holy city of Karbala and its impact on enhancing work outcomes. The research relied on the descriptive analytical approach in collecting, analyzing and interpreting its information, and the questionnaire was used as a main tool in collecting data and information from a sample of (182) employees, in addition to conducting personal interviews for a number of managers and employees of the department. A set of statistical methods were used, such as (normal distribution test, confirmatory factor analysis, descriptive statistics, simple correlation analysis Pearson, structural equation modeling, path analysis, determination coefficient (²R), test (T), depending on the ready statistical programs (SPSS V. 23). The research reached a set of conclusions, the most important of which are: The research section sought to make mistakes and unfamiliar topics an opportunity to learn, which means that the department exploits work errors in trying to develop and develop the capabilities of employees. Based on these conclusions, the research presented a set of recommendations, the most prominent of which are: The relentless pursuit by the department of the researched department to provide a flexible and effective communication system that gives employees the correct and accurate information, which contributes to raising the level of their performance efficiency, by providing an updated database.